Fusion for profit - Jagpal, Sharan (Oxford University Press, 2008)
The corporate world is typically structured in silos. Managers urgently need to overcome this "silo" effect by fusing ideas across different functional areas in the firm. In Fusion for Profit, Sharan Jagpal, a well-known and highly respected multidisciplinary researcher and business consultant, explains in simple language using real-world examples how managers can use sophisticated concepts to fuse different functional areas in the firm, especially marketing and finance, to increase the firm's value. The author provides novel solutions to a wide range of complex business problems ranging from choosing pricing and bundling strategies, to positioning and messaging strategies, to measuring brand equity, to measuring advertising productivity in a mixed media plan including Internet advertising, to compensating a multiproduct sales force, to measuring the potential gains and risks from mergers and acquisitions. These concepts are illustrated using case studies from a variety of firms in different industries, including AT&T, Coca-Cola, Continental Airlines, General Electric, Home Depot, Southwest Airlines, and Verizon